Hippocampus contributes to the maintenance but not the quality of visual information over time - Warren, David E. (Learn Mem, 2015)
The hippocampus has recently been implicated in the brief representation of visual information, but its specific role is not well understood. We investigated this role using a paradigm that distinguishes quantity and quality of visual memory as described in a previous study. We found that amnesic patients with bilateral hippocampal damage (N = 5) were less likely to remember test stimuli than comparison participants despite a brief maintenance interval (900 msec). However, estimates of memory quality were similar for all groups. Our findings suggest that the hippocampus contributes to brief maintenance of visual information but does not contribute to the quality of that information.